Pemberdayaan Guru Berbasis Kearifan Lokal Di Madrasah Ibtidaiyah Negeri Patihan Sidoharjo Sragen - Setyaningsih, Rosalia, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.Si (2015)
Various crisis experienced by the Indonesian nation, both moral crisis and the economic crisis is still ongoing and as if hard to overcome. To overcome the various critical that there is need for concrete action from all parties, not least the world of education, which is an institution that can be used instilling noble values in the younger generation. One of the educational institutions at the primary level under the auspices of the Ministry of Religion is Islamic Elementary School. The aim of research carried out at the State Elementary School Patihan Sidoharjo, Sragen 1) To describe the process of empowerment of local knowledge-based teacher carried out by a private teacher at the State Elementary School Patihan Sidoharjo Sragen. 2) To describe the process of empowerment of teachers based on local knowledge that transactions are carried out by the competent authority in the State Government Elementary School Patihan Sidoharjo Sragen. This study used qualitative methods. Data were collected through interviews, observation and documentation. The validity of the data using credibility. Data were analyzed interactively and continues over time to complete, so the data is saturated. Results of research on teacher empowerment based on local wisdom in the school are as follows: 1) Empowerment efforts of teachers based on local wisdom of individual teachers can be done by increasing the ability of mastering teaching materials based on local wisdom, by way of a. has a Bachelor diploma (S1) in the field of learning taught, b. Participate actively adding activities through various academic skills upgrading courses, workshops, c. Adding a personal insight by reading and listening to a wide variety of actual news, d. always sit at anyone not afraid to ask. 2. Efforts teacher empowerment based on local wisdom of teachers institutions can be done by way of a. hold coaching to teachers in order to understand the duties and functions well, b. Instilling a love of the nation's own culture through song Karawitan and folk songs, c. The use of the Java language programs subtle as a means of communication, d. Tadarus activities and discussions of Islam and minimal education carried out once a month, e. Cultivating National Spirit for teachers, f. Instilling love domestic products, g. Social Care activities, h. Caring responsible Activity environments and greening madrasah (green school) and i. Scout activities